Methylprednisolone as an Adjunct to Local Infiltration on Laminoplasty or Laminectomy before Wound Closure: A Randomized Controlled Trial - Niti Shrestha; Bo Han; Xiying Wang; Wenqing Jia; Fang Luo (Pain Research and Management)
TrialDesign. Patients undergoing laminoplasty and laminectomy often experience severe postoperative pain. Local infiltration analgesia during spine surgery significantly reduces postoperative pain, which only upholds for a short time. Whether methylprednisolone and local anaesthetics are better than local anaesthetics alone in postoperative analgesia is yet to be determined. The primary aim of this research was the postoperative evaluation of efficacy and safety of methylprednisolone when used as an adjunct to local anaesthesia, ropivacaine, before wound closure after surgical procedures, laminoplasty or laminectomy. Methods. 132 patients were divided with a ratio of 1 : 1 into methylprednisolone-ropivacaine and ropivacaine alone groups. Every 30 ml of local infiltration solution consisted of 15 ml of 1% ropivacaine with 14 ml of saline along with 1 ml of 40 mg methylprednisolone and 15 ml of 1% ropivacaine with 15 ml of saline in methylprednisolone-ropivacaine group and ropivacaine group, respectively. The standardization of the study solution depended on the number of levels involved in surgery. Primary outcome was the 48-hour cumulative sufentanil demand. Results. Demographic characters and surgical variables among the groups were identical. The average 48-hour cumulative sufentanil demand was 32.5 ± 20.6 μg in the methylprednisolone-ropivacaine group and 50.9 ± 27.2 μg in the ropivacaine group (p<0.001). The estimated median time of demand of the first analgesia via patient-controlled analgesia (PCA) pump was 2.5 hours and 2 hours in the methylprednisolone-ropivacaine group and the ropivacaine group, respectively (hazard ratio (HR) was 0.53, with 95% Cl 0.33 to 0.87 and Log-rank of p=0.0019). Conclusion. The infiltration of methylprednisolone as adjunct ropivacaine before wound closure is a safe and efficient strategy for pain management following laminoplasty or laminectomy.